2017
DOI: 10.1002/acr.22956
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Responsiveness of a 10‐Item Patient‐Reported Measure of Physical Function in a Rheumatoid Arthritis Clinic Population

Abstract: PF-10a was feasible to implement in a diverse RA population. It strongly correlates with the HAQ but has fewer ceiling effects and is responsive to changes in RA disease activity, suggesting its validity for use in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 33 publications
6
32
0
Order By: Relevance
“…In our evaluation of convergent and discriminant validity, PF‐10a scores correlated strongly with the HAQ (−0.746), moderately with CDAI, patient global assessment and pain scores (−0.457, −0.417, −0.371) and poorly correlated with SJC, TJC. This is consistent with a study reported by Wahl et al, (2017) who found that PF‐10a scores correlated strongly with the HAQ, patient global assessment by VAS, and pain scores (VAS) (−0.874, −0.720, −0.631), but did not correlate with SJCs or TJCs (−0.280, −0.293) . Also, in another study by Wahl et al (2018), they reported that the shorter physical function measure PROMIS‐PF‐10a outperformed HAQ in an ethnically diverse, urban RA clinic population .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our evaluation of convergent and discriminant validity, PF‐10a scores correlated strongly with the HAQ (−0.746), moderately with CDAI, patient global assessment and pain scores (−0.457, −0.417, −0.371) and poorly correlated with SJC, TJC. This is consistent with a study reported by Wahl et al, (2017) who found that PF‐10a scores correlated strongly with the HAQ, patient global assessment by VAS, and pain scores (VAS) (−0.874, −0.720, −0.631), but did not correlate with SJCs or TJCs (−0.280, −0.293) . Also, in another study by Wahl et al (2018), they reported that the shorter physical function measure PROMIS‐PF‐10a outperformed HAQ in an ethnically diverse, urban RA clinic population .…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with those of the RA patients studied byKamel et al in Egypt (2018) 19. Also, the mean value of PF-10a was 34.6 ± 6.2, indicating low physical function of studied patients compared to PF-10a mean value reported from the USA either from Caucasians, and multi-ethnic patients (42.4 ± 10.2 and 44.3 ± 9.3) 17,18. This may be due to Egyptian RA patients being significantly younger, had more active disease, and more frequent use of non-steroidal anti-inflammatory drugs, methotrexate and steroids and significantly lower use of bDMARDs.…”
supporting
confidence: 90%
“…Baseline clinical characteristics of patients included in the cross‐sectional sample were representative of RA populations previously described and similar to patients included in the longitudinal cohort (Table ). The majority of patients were female (83%), with a mean ± SD age of 56 ± 15 years.…”
Section: Resultsmentioning
confidence: 99%
“…The Patient Reported Outcome Measurement Information System (PROMIS) was developed by the National Institute of Health to provide standard metrics for measuring patient‐reported outcomes across chronic conditions. To date, a number of researchers have examined the properties of PROMIS measures in rheumatic conditions, with the largest concentration of work being on the physical functioning measures in RA . While PROMIS physical function measures have been evaluated in white and English‐speaking populations with RA, no studies have examined their validity or responsiveness in other racial and ethnic groups, non‐English speakers, or populations with low socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the PROMIS PF10a was recommended by our panelists. While the PROMIS physical function measures were developed using rigorous methods and tested extensively in the general population and populations with chronic disease , there were few studies specific to patients with RA , impacting panelist ratings. Panelists concluded that the shorter 10‐item instrument was likely more feasible for routine use in the clinic than the 20‐item survey.…”
Section: Discussionmentioning
confidence: 99%